CARBON EMISSION DISCLOSURE AND TAX MITIGATION AS DETERMINANTS OF FIRM VALUE: THE MODERATING EFFECT OF ESG DISCLOSURE ON ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2021–2024) - Haninun Haninun; Rika Emalia Ardi; Khairudin Khairudin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study examines the effects of carbon emission disclosure and tax mitigation on firm value and investigates the moderating role of Environmental, Social, and Governance (ESG) Disclosure in these relationships among energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. A quantitative research approach was employed using secondary data obtained from companies’ annual reports, sustainability reports, and market information. The sample was selected using a purposive sampling technique, resulting in 23 companies and 92 observations over the research period. The data were analyzed using panel data regression with EViews 14 and Moderated Regression Analysis (MRA). Carbon emission disclosure was measured using the Carbon Emission Disclosure index, tax mitigation was proxied by the Effective Tax Rate (ETR), ESG Disclosure was measured using an ESG disclosure index, while firm value was represented by Tobin’s Q. The findings demonstrate that carbon emission disclosure has a positive and significant effect on firm value. Tax mitigation also has a positive and significant effect on firm value. Furthermore, ESG Disclosure strengthens the relationship between carbon emission disclosure and firm value and enhances the effect of tax mitigation on firm value. These findings indicate that value creation in the energy sector is not solely determined by financial and economic management but is also influenced by corporate sustainability practices and transparency. More comprehensive ESG Disclosure can enhance the credibility of corporate information and consequently strengthen investors’ positive responses to the environmental and tax-related strategies implemented by companies.